The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/catal11101178
|View full text |Cite
|
Sign up to set email alerts
|

Pd/Alumina Catalysts for Beneficial Transformation of Harmful Freon R-22

Abstract: Chlorodifluoromethane (R-22), the most abundant freon in the atmosphere, was subjected to successful hydrodechlorination in the presence of palladium supported on γ-alumina, at a relatively low reaction temperature (180 °C). The combination of catalytic actions of alumina (performing freon dismutation) and Pd nanoparticles (catalyzing C–Cl bond splitting in the presence of hydrogen) results in the transformation of freon into valuable, chlorine-free products: methane and fluoroform, the mixture of which is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Karpinski et al reported successful hydrochlorination of freon (chlorodifluoromethane) at a relatively low reaction temperature (180 °C) using the alumina-supported Pd catalyst. 182 The combination of catalytic actions of alumina, which performs freon dismutation, and Pd nanoparticles, which catalyze C–Cl bond splitting in the presence of hydrogen, results in the transformation of freon into valuable, chlorine-free products (methane and fluoroform), as well as excellent catalytic stability (as shown in Fig. 26A).…”
Section: Some Promising Applications Of Alumina-supported Pd-based Ca...mentioning
confidence: 99%
“…Karpinski et al reported successful hydrochlorination of freon (chlorodifluoromethane) at a relatively low reaction temperature (180 °C) using the alumina-supported Pd catalyst. 182 The combination of catalytic actions of alumina, which performs freon dismutation, and Pd nanoparticles, which catalyze C–Cl bond splitting in the presence of hydrogen, results in the transformation of freon into valuable, chlorine-free products (methane and fluoroform), as well as excellent catalytic stability (as shown in Fig. 26A).…”
Section: Some Promising Applications Of Alumina-supported Pd-based Ca...mentioning
confidence: 99%